The archaeology of Caribbean and circum-Caribbean farmers 6000 BC - AD 1500
1 online resource (478 pages)
Keywords: "Comprising 17 chapters and with a wide geographic reach stretching from the Florida Keys in the north to the Guianas in the south, this volume places a well-needed academic spotlight on what is generally considered an integral topic in Caribbean and circum-Caribbean archaeology.The book explores a variety of issues, including the introduction and dispersal of early cultivars, plant manipulation, animal domestication, dietary profiles, and landscape modifications. Tried-and-true and novel analytical techniques are used to tease out aspects of the Caribbean and circum-Caribbean database that inform the complex and often-subtle processes of domestication under varying socio-environmental conditions. Contributors discuss their findings within multiple constructs such as neolithisation, social interaction, trade, mobility, social complexity, migration, colonisation, and historical ecology. Multiple data sources are used which include but are not restricted to rock art, cooking pits and pots, stable isotopes, dental calculus and pathologies, starch grains, and proxies for past environmental conditions.Given its multi-disciplinary approaches, this volume should be of immense value to both researchers and students of Caribbean archaeology, biogeography, ethnobotany, zooarchaeology, historical ecology, agriculture, environmental studies, history, and other related fields."--Provided by publisher.